KHAZANAH EKOLEKSIKON FLORA DAN FAUNA DALAM BOEKOE PANTOEN KARYA THE TIN LAM - Nurzuha Nurzuha; Mohd Fauzi; Denni Iskandar (Universitas Lancang Kuning, 2023)
This research began with the phenomenon of the endangered language found in the pantun script which contains a lot of richness in the elements of the flora and fauna lexicon. The purpose of this study is to determine the richness of the flora and fauna lexicon and its meaning in Boekoe Pantoen by The Tin Lam. This kind of research is qualitative research in which this research uses the ecolinguistic concept of Aron Meko Mbete. The data of this research is in the form of flora and fauna eco-collection that sourced from Boekoe Pantoen by The Tin Lam. The results showed that there were 73 flora lexicon and 69 fauna lexicon. In the meaning of flora and fauna there is a social meaning, the meaning of love for the environment and culture. Basically people in ancient times were sympathetic to the environment, this nature became their inspiration material to express feelings using flora and fauna features, being grateful for God's favors, as medicine, entertainment, and these flora and fauna features do exist and are not just an illusion but are nowadays the phenomenon has changed. The flora and fauna lexicon is rarely used.